Imagined futures. Fictionality in economic action - Beckert, Jens (Köln, 2011)
"Starting from the assumption that decision situations in economic contexts are characterized by fundamental uncertainty, the paper argues that the decision-making of intentionally rational actors is anchored in fictions. "Fictionality" in economic action is the inhabitation in the mind of an imagined future state of the world and the beliefs in causal mechanisms leading to this future state. Actors are motivated in their actions by the imagined future and organize their activities based on these mental representations. Since these representations are not confined to empirical reality, fictionality is also a source of creativity in the economy. Fictionality opens up a way to an understanding of the microfoundations of the dynamics of the economy. The paper develops the notion of fictional expectations and applies it to investments, consumption and money. The last part relates the notion of fiction to calculation and social macrostructures as two other devices of decision-making and hints at the relevance of fictionality for the macrodynamics of capitalism."